2013
DOI: 10.1021/ac400514u
|View full text |Cite
|
Sign up to set email alerts
|

A Label-Free Potentiometric Sensor Principle for the Detection of Antibody–Antigen Interactions

Abstract: ABSTRACT:We report here on a new potentiometric biosensing principle for the detection of antibody−antigen interactions at the sensing membrane surface without the need to add a label or a reporter ion to the sample solution. This is accomplished by establishing a steady-state outward flux of a marker ion from the membrane into the contacting solution. The immunobinding event at the sensing surface retards the marker ion, which results in its accumulation at the membrane surface and hence in a potential respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 17 publications
(30 reference statements)
2
45
0
Order By: Relevance
“…Click chemistry was also used in the fabrication of a virus biosensor 41. Biotin was ‘clicked’ on the N 3 PVC membrane surface, and sensor was subsequently treated with streptavidin and a biotinylated virus antibody, thus creating a sandwich structure on the sensor surface.…”
Section: Pvc Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Click chemistry was also used in the fabrication of a virus biosensor 41. Biotin was ‘clicked’ on the N 3 PVC membrane surface, and sensor was subsequently treated with streptavidin and a biotinylated virus antibody, thus creating a sandwich structure on the sensor surface.…”
Section: Pvc Modificationmentioning
confidence: 99%
“…Carboxylated PVC was also used to covalently bind biotin in an avidin sensor 53 based on the surface blocking principle described above 41. Calcium and sodium selective membranes were modified by a reaction with aminated biotin in presence of EDC.…”
Section: Pvc Modificationmentioning
confidence: 99%
“…During the preparation of this paper, Bakker et al reported a label-free potentiometric biosensing method for the detection of antibody−antigen interactions at the polymeric membrane surface using zero-current ion fluxes across polymeric membrane ISE. 43 In comparison with the method, the pulsed galvanostatic approach can control marker ions more precisely. In addition, the marker ions are specific to the labeled enzyme, which can reduce the effect of nonspecific interactions at the polymer surface.…”
Section: Selection Of the Buffer Solutionmentioning
confidence: 99%
“…In recent years, potentiometry based on ion-selective electrodes (ISEs) have evolved to provide a promising transducer for biosensing [22][23][24][25][26]. Typically, these electrodes have been extensively investigated for biosensing via zero-current potentiometry.…”
Section: Introductionmentioning
confidence: 99%